2017
DOI: 10.1177/0885328217713357
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-loaded glycyrrhizic acid-conjugated human serum albumin nanoparticles wrapping resveratrol nanoparticles: Preparation, characterization, and targeting effect on liver tumors

Abstract: In this study, glycyrrhizic acid-conjugated human serum albumin nanoparticles wrapping resveratrol nanoparticles were prepared to establish a tumor targeting nano-sized drug delivery system. Glycyrrhizic acid was coupled to human serum albumin, and resveratrol was encapsulated in glycyrrhizic acid-conjugated human serum albumin by high-pressure homogenization emulsification. The average particle size of sample nanoparticles prepared under the optimal conditions was 108.1 ± 5.3 nm with a polydispersity index (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A lot of studies are devoted to the use of GA and its metabolite glycyrrhetic acid as a targeting unit in liver therapy Cai et al, 2016;Wu et al, 2017). As it was mentioned above, GA is effective hepatoprotective agent (see Section 4).…”
Section: Self-association Of Ga and Its Use In Drug Deliverymentioning
confidence: 99%
“…A lot of studies are devoted to the use of GA and its metabolite glycyrrhetic acid as a targeting unit in liver therapy Cai et al, 2016;Wu et al, 2017). As it was mentioned above, GA is effective hepatoprotective agent (see Section 4).…”
Section: Self-association Of Ga and Its Use In Drug Deliverymentioning
confidence: 99%
“…GL-HSA-RES-NPs was obtained by the high-pressure homogeneous emulsification method (Wu et al, 2017). Briefly, the glycyrrhizic acid (GL) of 59.6 mg was added to the methanol solution of 4.0 mL and treated in ultrasonic bath for 30 s (Li et al, 2005).…”
Section: Preparation Of Gl-hsa-res-npsmentioning
confidence: 99%
“…Recently, our research team reported the preparation, characterization and liver cancer targeting of glycyrrhizic acid-conjugated human serum albumin loaded RES nanoparticles (GL-HSA-RES-NPs) (Wu et al, 2017). GL-HSA-RES-NPs were prepared by a high-pressure homogeneous emulsification method with an average particle size of 108.1 ± 5.3 nm and a polydispersity index (PDI) of 0.001.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study also showed the beneficial effect of combining the drugs with albumin to prevent deposition of the drug at the injection site and obtain a slow release of the drug. 152…”
Section: In Vitro Studiesmentioning
confidence: 99%